Effect of cumulative time of Helicobacter pylori infection on gastric precancerous lesions? - Arif Mansur Coşar (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Coşar AM. Effect of cumulative time of Helicobacter pylori infection on gastric precancerous lesions? Turk J Gastroenterol 2018; 29: 524-5.